STUDY ON SEDIMENTOLOGY FROM THE MESJID RIVER ESTUARY AND ITS ENVIRONS IN THE RUPAT STRAIT, THE EAST COAST OF SUMATERA ISLAND - Rifardi . (JOURNAL OF COASTAL DEVELOPMENT, 2001)
The sedimentological aspects of the Mesjid River Estuary and its neighboring seas are revealed by various analytical approaches; i.e. mechanical grain size analysis, ignition loss method, metallic element analysis and sand grain composition analysis. The estuary area is characterized by fine sediments (very fine sand to very fine silt). Based on the relation between the character of bottom sediments and the environmental condition, the the Mesjid River Estuary and its Environs is divided into the following three areas: 1) The western part of the study area characterized by rather coarse-grained sediments and low mud content　under the influence of longshore current and poorly sorted sediments supplied by the Mesjid River, 2) The southern part of the study area characterized by coarse-grained sediments under the influence of strong tidal currents, 3) The northern and eastern parts of  the study area characterized by fine-grained sediments and high mud content under conditions of sea water masses. The texture and organic matter content of the sediments play important role on the growth of the mangrove which thrive along the coast of the study area.